2009
DOI: 10.1002/mus.21473
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PI3K/Akt/TOR pathway in stretch‐induced hypertrophy of myotubes

Abstract: Skeletal muscle cells are hypertrophied by mechanical stresses, but the underlying molecular mechanisms are not fully understood. Two signaling pathways, phosphatidylinositol 3-kinase (PI3K)/Akt to target of rapamycin (TOR) and extracellular signal-regulated kinase kinase (MEK) to extracellular signal-regulated kinase (ERK), have been proposed to be involved in muscle hypertrophy. In this study we examined the involvement of these pathways in primary cultures of chick skeletal myotubes subjected to passive cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
1
40
1
Order By: Relevance
“…Among the intramuscular signaling networks, mTORC1 appears to be the primary regulator of muscle protein synthesis and growth (Goodman 2014). Although MAPK signaling may promote activation of mTORC1 signaling, MAPK signaling does not appear to be absolutely necessary for mechanically induced mTORC1 activation (Sasai et al 2010;You et al 2012). It remains unclear whether maximal stimulation of muscle protein synthesis is mediated by the convergence of mTORC1 and MAPK signaling pathways on downstream targets, such as p70S6 kinase (p70S6k) and ribosomal protein S6 (RPS6).…”
Section: Discussionmentioning
confidence: 99%
“…Among the intramuscular signaling networks, mTORC1 appears to be the primary regulator of muscle protein synthesis and growth (Goodman 2014). Although MAPK signaling may promote activation of mTORC1 signaling, MAPK signaling does not appear to be absolutely necessary for mechanically induced mTORC1 activation (Sasai et al 2010;You et al 2012). It remains unclear whether maximal stimulation of muscle protein synthesis is mediated by the convergence of mTORC1 and MAPK signaling pathways on downstream targets, such as p70S6 kinase (p70S6k) and ribosomal protein S6 (RPS6).…”
Section: Discussionmentioning
confidence: 99%
“…The best characterized system responses to mechanical stimuli are the cardiovascular (17-21), musculoskeletal (22)(23)(24), and pulmonary physiology (25,(33)(34)(35)(36)(37)(38) changes to airway smooth muscle, due to hypertrophy and/or hyperplasia, are a well known feature of chronic airway diseases, such as asthma, chronic obstructive pulmonary disease, and cystic fibrosis (12)(13)(14)(15)(16). Alterations in the regulation of gene expression by mechanical stimuli play an important role in the thickening and remodeling of the airway wall in subjects with the above airway diseases (25).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that both hypertrophy and hyperplasia of human airway smooth muscle cells (HASMCs) play key roles in airway remodeling (12)(13)(14)(15)(16). Many lines of evidence have demonstrated that hypertrophy in cardiomyocytes, skeletal myotubes, and smooth muscle cells is induced by various hypertrophic stimuli, including mechanical stretch (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Recently, it has been shown that miRNAs play important roles in the induction of cardiac hypertrophy as well as response to hypertrophic stimuli (28 -32).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming apparent that many alternative splicing events require the activity of the same signaling pathways (Lynch, 2007). For example, the phosphatidylinositol 3-kinase (PI3K)/Akt/mTOR (mammalian target of rapamycin) signaling cascade mediates skeletal muscle protein synthesis in response to nutritional and mechanical stimuli (Anthony et al, 2000;Bolster et al, 2003;Kimball and Jefferson, 2006;Kimball et al, 2000;Sasai et al, 2010), and also activates and interacts with members of the serine/arginine (SR)-rich protein family (Blaustein et al, 2009;Karni et al, 2008;Lynch, 2007), a ubiquitous set of alternative splicing factors that affect exon inclusion/exclusion and facilitate translation of specific mRNAs (Blaustein et al, 2005;Sanford et al, 2005). Modulation of sarcomere gene alternative splicing by nutritional and/or mechanically induced signaling through PI3K/Akt/mTOR would add important functionality to the already complex nature of this pathway, and may mediate the dietary and weight-loading effects on troponin T alternative splicing observed in both insects and mammals.…”
Section: Discussionmentioning
confidence: 99%